Building Fluency In Writing II Based On Micro And Macro Skills Of Writing By Using Peer Assessment - Tintin Susilowati (Kodifikasia: Jurnal Penelitian Islam, 2018)
Writing is difficult for English Department students in Indonesia. Students commonly have low ability to write and have very limited time to practice this skill. To overcome students’ problems in writing, the use of peer assessment can be an appropriate way to improve fluency in writing since this research is held to: (1) elaborate the roles of peer assessment to build fluency in writing classes, (2) identify the types of activity in writing class by implementing peer assessment, (3) explore the strengths of peer assessment to build fluency in writing, and (4) to prove the effectiveness of peer assessment to build fluency in writing.This is a mixed method research. The subjects of this research are nine students of TI.B class in academic years 2016/ 2017. To collect the data, some instruments such as field note, observation, documentation and test were used. Interactive analysis and statistical analysis (t-test) were applied to analyze quantitative data. Furthermore, statistical analysis using SPSS 20 used to analyze quantitative data.The results of the research are: (1) the use of peer assessment minimizes students’ apprehension in writing, (2) constructive activities are important to lead students in conducting active and critical learning, (3) peer assessment is meaningful to build students to be authentic writers and readers, (4) peer assessment is effective to build students’ fluency in writing indicated by the result of hypothesis test.